2009
DOI: 10.1002/eji.200838832
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional re‐programming of primary macrophages reveals distinct apoptotic and anti‐tumoral functions of IRF‐3 and IRF‐7

Abstract: The immunoregulatory transcriptional modulators -IFN-regulatory factor (IRF)-3 and IRF-7 -possess similar structural features but distinct gene-regulatory potentials. For example, adenovirus-mediated transduction of the constitutively active form of IRF-3 triggered cell death in primary human MU, whereas expression of active IRF-7 induced a strong anti-tumoral activity in vitro. To further characterize target genes involved in these distinct cellular responses, transcriptional profiles of active IRF-3-or IRF-7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 63 publications
5
63
0
1
Order By: Relevance
“…Phosphorylation of IRF3 is associated with protein dimerization and entry into the nucleus, where it acts as a transcription factor for genes involved in immunity, inflammation, and apoptosis (23)(24)(25)(26)34). We, therefore, used native-PAGE to monitor the dimerization of IRF3 and observed that IRF3 dimerization was ISD-dependent and further stimulated by UV (Fig.…”
Section: Uv Radiation Does Notmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of IRF3 is associated with protein dimerization and entry into the nucleus, where it acts as a transcription factor for genes involved in immunity, inflammation, and apoptosis (23)(24)(25)(26)34). We, therefore, used native-PAGE to monitor the dimerization of IRF3 and observed that IRF3 dimerization was ISD-dependent and further stimulated by UV (Fig.…”
Section: Uv Radiation Does Notmentioning
confidence: 99%
“…The binding of STING to 2Ј,3Ј-cGAMP and related cyclic dinucleotides that are produced by microbial pathogens (16 -19) causes a conformational change in STING (20,21) that is thought to allow it to function as a scaffold protein to mediate the phosphorylation and activation of IRF3 (interferon regulatory factor 3) by the upstream kinase TBK1 (TANK-binding kinase 1) (22). This phosphorylation event induces IRF3 homodimerization and is required for IRF3 to function as a transcription factor for a variety of gene targets, including type I interferons, pro-inflammatory cytokines, and pro-apoptotic factors (23)(24)(25)(26).…”
mentioning
confidence: 99%
“…The TAM phenotype is reversible and these cells can be re-educated to exert antitumor activity [41][42][43]. In a recent study [44], anti-CD40 antibodies with agonist activity have been shown to have antitumor potential in both murine and human carcinoma of the pancreas.…”
Section: Therapeutic Targetingmentioning
confidence: 99%
“…Epigenetic control of M2, alternative activation of macrophages is mediated by Jmjd3, a H3K27-specific demethylase. Moreover, the members of the IRF family are implicated as critical target genes for the control of M2 activation [10,11].…”
Section: Recognition and Regulationmentioning
confidence: 99%